2011
DOI: 10.1002/app.33866
|View full text |Cite
|
Sign up to set email alerts
|

Poly(L‐lactide)/polypropylene blends: Evaluation of mechanical, thermal, and morphological characteristics

Abstract: Poly(Llactide) (PLA) was blended with polypropylene (PP) at various ratios (PLA: PP ¼ 90 : 10, 80 : 20, 70 : 30,and 50 : 50) with a melt-blending technique in an attempt to improve the melt processability of PLA. Maleic anhydride (MAH)-grafted PP and glycidyl methacrylate were used as the reactive compatibilizers to induce miscibility in the blend. The PLA/PP blend at a blend ratio of 90 : 10, exhibited optimum mechanical performance. Differential scanning calorimetry and thermogravimetric analysis studies sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 40 publications
2
66
0
Order By: Relevance
“…Analysis of all the SEM images show clearly a decrease in the size of the particles when the concentration of PMMA-co-BMA decreases, and there is a good homogeneity for all the bioblends at least in the magnification of the measurement, and no obvious phase separation boundary could be seen. This last comment also strongly suggest a good compatibility between the two polymers, which is in a good agreement with literature [48] .…”
Section: Scanning Electron Microscopic Analysissupporting
confidence: 87%
“…Analysis of all the SEM images show clearly a decrease in the size of the particles when the concentration of PMMA-co-BMA decreases, and there is a good homogeneity for all the bioblends at least in the magnification of the measurement, and no obvious phase separation boundary could be seen. This last comment also strongly suggest a good compatibility between the two polymers, which is in a good agreement with literature [48] .…”
Section: Scanning Electron Microscopic Analysissupporting
confidence: 87%
“…The explanation of the different trends found for our blends is twofold: PLA is present in the Liquid Wood mixture as shown by the thermal and microscopic characterization reported above; MAPP and lignin itself can interact to enhance the interfacial adhesion of the blends components. As reported by Reddy et al [28] and Choudhary et al [29], PP/PLA blends can show enhanced mechanical properties, despite the incompatibility of the pure polymers, when proper compatibilizers, like MAPP, are used. The ester groups of PLA can interact with lignin, and the anhydride groups of MAPP can react with cellulose.…”
Section: Resultsmentioning
confidence: 77%
“…However, addition of MAPP introduced compatibility between PP and PLLA in their blend, and as shown in the micrograph of PP80C6, PLLA was almost uniformly dispersed in the PP matrix, which resulted in increase in the tensile strength of PP80C6 sample, as described earlier. Therefore, it may be concluded that MAPP has improved the interfacial adhesion between PP and PLLA due to reaction between PLLA functional group and the anhydride group present in MAPP [9].…”
Section: Morphological Analysismentioning
confidence: 99%
“…Blends of PP with poly(L-lactide) (PLLA) have been studied earlier to improve dyeability of PLLA [8], melt processability of PLLA [9], and rheological and mechanical properties [3]. PP and PLLA form incompatible blends, and a compatibilizer is needed to improve compatibility between them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation